EVOLUÇÃO DO PERFIL SOCIOECONÔMICO DE INGRESSANTES DE UM CURSO DE ENGENHARIA DE PRODUÇÃO APÓS A ADOÇÃO DO ENEM COMO FORMA DE INGRESSO - Da Costa Jahara, Rafael; Regina Corbo, Anna; Andre Villas Boas Mello, José (LINKSCIENCEPLACE, 2026)
This work aims to discuss and evaluate aspects related to changes in the socioeconomic profile of the new entering a course of Industrial Engineering after the transition from conventional vestibular for the ENEM. As methodology, were applyed anonymous questionnaires for further analysis. The results obtained shows that there was a change of profile and the new profile is in line with the objectives of the adoption of SISU by the institution.